The contribution of epigenetics in Sjögren’s Syndrome - Konsta, Orsia D.; Thabet, Yosra; Le Dantec, Christelle; Brooks, Wesley H.; Tzioufas, Athanasios G.; Pers, Jacques-Olivier; Renaudineau, Yves (Frontiers in Genetics, 2014)
Sjögren’s syndrome (SS) is a chronic autoimmune epithelitis that combines exocrine gland dysfunctions and lymphocytic infiltrations. While the pathogenesis of SS remains unclear, its etiology is multifunctional and includes a combination of genetic predispositions, environmental factors, and epigenetic factors. Recently, interest has grown in the involvement of epigenetics in autoimmune diseases. Epigenetics is defined as changes in gene expression, that are inheritable and that do not entail changes in the DNA sequence. In SS, several epigenetic mechanisms are defective including DNA demethylation that predominates in epithelial cells, an abnormal expression of microRNAs, and abnormal chromatin positioning-associated with autoantibody production. Last but not least, epigenetic modifications are reversible as observed in minor salivary glands from SS patients after B cell depletion using rituximab. Thus epigenetic findings in SS open new perspectives for therapeutic approaches as well as the possible identification of new biomarkers.